A Comparative national tasks database - Marta Fana; Valeria Cirillo; Dario Guarascio; Matteo Tubiana (European Commission, Joint Research Centre (JRC), 2020)
The present study offers an original and unique database collecting information on task profiles using national data across five European countries (France, Germany, Italy, Spain and UK) in order to assess the existence of cross country variability in terms of tasks content, methods of work and tools used at work. Overall, the comparative component contributes to better understanding nature of work, effects of technical change, institutional and cultural variations across countries, a dimension often neglected in the literature especially for limitation in data availability at the national level. The creation of task indicators follows the overall approach and methodology developed in FernándezMacías, Hurley and Bisello, 2016; Fernández-Macías, Bisello, Sarkar, Torrejón, 2016 and its updated version by Fernández-Macías and Bisello (2020). In order to provide consistent cross-country data enabling comparisons, we applied the weighted ranking method already established in the literature and often used in the job-based approach. Using the ordered ranking resulting from the standardisation adopted, we analysed national employment structures focusing on tasks profile as well as on the employment distribution by task-terciles. The descriptive analysis performed highlights two main patterns. First, a certain degree of similarity in employment structures by tasks content terciles emerges, especially once compared across occupational groups. The task content of jobs reflects the technical nature of the production process - which is directly related to the type of product or service that is produced - and, in principle, is less affected by national differences. Second, countries show more heterogeneity in terms of work organization, namely "methods of work". This can in turn be explained by the fact that work methods reflect (relatively more than content itself) the socio-organizational structure in which they are embedded and are affected by idiosyncratic behavioral patterns of routines, cultural values, institutional frameworks.
Keywords: 330; tasks; technical change; cross-country comparative analysis